Synthesis and Theoretical Study of Gadolinium(III) Complex of Heptadentate (N4O3) Tripodal Schiff Base Ligand - IZADKHAH*, VIDA; SALEHZADEH, SADEGH; GOLBEDAGHI, REZA; BAYAT, MEHDI; DAVOODI, LEILA (Asian Journal of Chemistry, 2010)
A new potentially heptadentate (N4O3) Schiff base ligand{N[(CH2)2N = CH(2-OH-5-BrC6H3)]2[(CH2)3N = CH(2-OH-5-BrC6H3)]} (H3L) was synthesized and characterized byelemental analysis and various spectroscopic methods. Thisligand was derived from the condensation reaction of a tripodaltetraamine ligand, bis(2-aminoethyl)(3-aminopropyl)amine (pee) with 3 equiv. of 5-bromosalicylaldehyde. Theneutral gadolinium(III) complex of this bulky ligand was alsosynthesized. The complex was characterized by microanalysisand IR spectra. The capability of H3L as well as itsunsubstituted analogs to encapsulate a lanthanide ion, hereinLa(III), has been theoretically studied by ab initio restrictedHartree-Fock (RHF) and density functional B3LYP methods.